Pseudozaphanera narendramodii sp. n. (Hemiptera: Aleyrodidae) with New Record of the Genus from the Oriental Region, India - Ragupathy, Ethiraj; Radhakrishnan, R. (Indian Forester, 2019)
The whitefly genus Pseudozaphanera Manzari is recorded here for the first time from the Oriental Region, India. A new species, P. narendramodii Ragupathy sp. n. feeding on Pleiospermium alatum (Rutaceae) is described from Tamil Nadu, India with line drawings and photomicrographs of the holotype. An updated identification key to puparia of Pseudozaphanera species so far known is provided.